2014
DOI: 10.5812/aapm.18263
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Postoperative Opioid Consumption by Adding an Ultrasound-Guided Rectus Sheath Block to Multimodal Analgesia for Abdominal Cancer Surgery With Midline Incision

Abstract: Background:Many multimodal analgesia techniques have been tried to provide adequate analgesia for midline incisions extending above and below the umbilicus aiming at limiting the perioperative use of morphine thus limiting side effects. Ultrasound (US) guidance made the anesthesiologist reconsider old techniques for wider clinical use. The rectus sheath block (RSB) is a useful technique under-utilized in the adult population.Objectives:Our study examined the efficacy of a preemptive single-injection rectus she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 23 publications
5
36
0
Order By: Relevance
“…Study reports have also demonstrated that this block provides effective pain control in surgeries involving midline incisions [60,61]. The rectus sheath block can be used in combination with the TAP block for pain relief over a wider area in surgeries involving the anterior abdominal wall [57,62].…”
Section: Evidence and Clinical Applicationsmentioning
confidence: 99%
“…Study reports have also demonstrated that this block provides effective pain control in surgeries involving midline incisions [60,61]. The rectus sheath block can be used in combination with the TAP block for pain relief over a wider area in surgeries involving the anterior abdominal wall [57,62].…”
Section: Evidence and Clinical Applicationsmentioning
confidence: 99%
“…Bilateral single injection ultrasound‐guided rectus sheath blocks (UGRBs) are used for postoperative analgesia after midline abdominal incisions from the xyphoid superiorly, to the pubic symphysis inferiorly . To ensure adequate blockade of multiple branches of intercostal nerves , the spread of anesthetic should match the length of the incision .…”
Section: Introductionmentioning
confidence: 99%
“…Bilateral single injection ultrasound-guided rectus sheath blocks (UGRBs) are used for postoperative analgesia after midline abdominal incisions from the xyphoid superiorly, to the pubic symphysis inferiorly. [1][2][3][4][5][6][7][8][9] To ensure adequate blockade of multiple branches of intercostal nerves, the spread of anesthetic should match the length of the incision. Knowledge of the local anesthetic spread can help to determine the optimal site at which the local anesthetic via single injection should be administered, along with the volume of local anesthetic required to achieve the desired spread in the posterior rectus sheath.…”
Section: Introductionmentioning
confidence: 99%
“…Bashandy et al randomized 60 patients who were undergoing midline laparotomies for radical cancer resections to receive RSB with general anesthesia or general anesthesia alone [61]. Not only were pain scores significantly lower in the RSB group postoperatively, but also morphine consumption was less and consequently patients developed fewer side effects like respiratory depression, excessive sedation and postoperative nausea and vomiting [61].…”
Section: Clinical Evidencementioning
confidence: 99%
“…Bashandy et al randomized 60 patients who were undergoing midline laparotomies for radical cancer resections to receive RSB with general anesthesia or general anesthesia alone [61]. Not only were pain scores significantly lower in the RSB group postoperatively, but also morphine consumption was less and consequently patients developed fewer side effects like respiratory depression, excessive sedation and postoperative nausea and vomiting [61]. In a retrospective case review of 98 patients undergoing major gynecologic surgery for benign or malignant disease, patients who received a rectus sheath block performed by the surgeons intraoperatively had lower pain scores on waking, required less morphine postoperatively, had their patient controlled analgesia (PCA) discontinued sooner, and went home earlier than patients receiving standard subcutaneous infiltration of the wound [62].…”
Section: Clinical Evidencementioning
confidence: 99%